Human Amniotic Epithelial Cells Secretome: Components, Bioactivity, and Challenges - Fathi, Ibrahim; Miki, Toshio (Frontiers in Medicine, 2022)
Human amniotic epithelial cells (hAECs) derived from placental tissue have received significant attention as a promising tool in regenerative medicine. Several studies demonstrated their anti-inflammatory, anti-fibrotic, and tissue repair potentials. These effects were further shown to be retained in the conditioned medium of hAECs, suggesting their paracrine nature. The concept of utilizing the hAEC-secretome has thus evolved as a therapeutic cell-free option. In this article, we review the different components and constituents of hAEC-secretome and their influence as demonstrated through experimental studies in the current literature. Studies examining the effects of conditioned medium, exosomes, and micro-RNA (miRNA) derived from hAECs are included in this review. The challenges facing the application of this cell-free approach will also be discussed based on the current evidence.